Peran Mahkamah Konstitusi Federal Jerman dalam Perlindungan Hak Fundamental Warga Negara berdasarkan Kewenangan Pengaduan Konstitusional - Tanto Lailam (Badan Strategi Kebijakan Hukum, 2022)
The research focuses on the role of the constitutional complaint authority of the German Constitutional Court (Bundesverfassungsgericht/ BVerfG). The research question is how do BVerfG's system and role protect citizens' fundamental rights? The research aims to know the system (urgency, regulations) and the role/ performance of BVerfG in carrying out its authority. This research is normative legal research with regulation and case approach. The results show that BVerfG has received 240,251 (98%) cases from 1951 - 2020 (6,000 cases per year), with a successful application rate of approximately 2% of the total decisions. This paper discusses three cases regarding the decision-related global supervision, the prohibition of wearing the hijab in a legal traineeship, and the case of the European Central Bank/ECB's asset purchase program. BVerfG shows that there is the best role in protecting the fundamental rights of citizens from court decisions that violate fundamental rights. The best practices of the BVerfG are recognition and reference in arranging the Constitutional Court in other countries from the Continental European and Anglo-Saxon legal systems. For Indonesia, it becomes a reference in adding the constitutional complaint authority to the Indonesian Constitutional Court in the future.